The method of writing history According to Hisamaddin Naqshbandi (Raparin Journal of Humanities (RJH), 2023)
We cannot call everyone who writes history and records events a historian، because the work of a historian is difficult and responsible.It requires a certain scientific curriculum and approach based on a number of spiritual tools such as honesty، objectivity and impartiality.Hassameddin Naqshbandi is one of the prominent Kurdish historian who played an important role in writing Kurdish history in the middle ages in general and the Islamic period in particular، even as an expert in Islamic history in his historical writings and publications، within the framework of his historical research in all three historical periods (medieval، modern and contemporary) he relied on analysis in the transmission of historical texts، in addition to describing historical events in an objective manner Religion، regionalism and nationalism in this field، not only worked as an ordinary historian، but at the same time he was a proofreader، critic and worshipper.This research consists of two main works of hassamedin Naqshbandi and the second is about his method of writing history.